2002
DOI: 10.1074/jbc.m109853200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Plant Alternative Oxidase

Abstract: All higher plants and many fungi contain an alternative oxidase (AOX), which branches from the cytochrome pathway at the level of the quinone pool. In an attempt, first, to distinguish between two proposed structural models of this di-iron protein, and, second, to examine the roles of two highly conserved tyrosine residues, we have expressed an array of site-specific mutants in Schizosaccharomyces pombe. Mitochondrial respiratory analysis reveals that S. pombe cells expressing AOX proteins in which Glu-217 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…This motif is important for the activity of di-iron carboxylate family members (28). However, variants of alternative oxidase, an enzyme that also binds iron with EXXH motifs, can still partially function when mutated in the key glutamic acid residue of one of the EXXH motifs (29,30). This suggests that alteration of the EXXH motif does not necessarily lead to a total loss of function.…”
Section: Table VI Effect Of Q Isoforms On the Defecation Cycle Lengthmentioning
confidence: 94%
“…This motif is important for the activity of di-iron carboxylate family members (28). However, variants of alternative oxidase, an enzyme that also binds iron with EXXH motifs, can still partially function when mutated in the key glutamic acid residue of one of the EXXH motifs (29,30). This suggests that alteration of the EXXH motif does not necessarily lead to a total loss of function.…”
Section: Table VI Effect Of Q Isoforms On the Defecation Cycle Lengthmentioning
confidence: 94%
“…Site-directed mutagenesis studies have confirmed the essential nature of these amino acids as well as identifying other residues (e.g., tyrosine residues) essential for activity [93,94]. EPR and FTIR spectroscopy studies have shown that the active site for the reduction of oxygen to water does indeed comprise a binuclear iron center [95,96] and other work has identified residues important for ubiquinol binding [94,97].…”
Section: Alternative Oxidasementioning
confidence: 99%
“…The fact that this residue is buried deeply into the protein structure provides it with a peculiar stability (up to several days) (43). Mutagenesis studies of both the plant AOX (44) and TAO (15) , and the radical state of TyrD in photosystem II shows two bands at 1551 and 1503 cm Ϫ1 (46 -48). Moreover, density functional theory simulations (see "Experimental Procedures") of a neutral tyrosyl radical in both free zwitterionic tyrosine and in a model peptide also predict a strong band at 1554 cm…”
mentioning
confidence: 99%